Racial ambivalence in diverse communities : whiteness and the power of color-blind ideologies - Burke, Meghan A. (Lexington Books, 2012)
This provocative ethnography reveals how pervasive color-blind ideology remains even among pro-diversity liberals active in shaping racially diverse communities, as well as its result: the unintentional re-creation of a white habitus in a racially diverse community. The book also explores the contours of white racial identity and the concrete links between racial discourse, ideology, and social action in the contemporary United States.